KEPUASAN KERJA PENGARUHNYA PADA PRODUKTIVITAS KERJA KARYAWAN SEBUAH PERUSAHAAN - Mohammad Kanzunnudin (STIE Pelita Nusantara Semarang, 2006)
In general, each company has similar objectives and goals such as survival, profit orientation and growth. To meet such objectives and goals, each company has to obtain and use available resources. In this case, employees productivity plays great role to contribute to the success of a company. Based on observation, it could be found that employees productivity hand strong correlation with the success or production the company wanted to meet.Employees productivity played important role in meeting future companys objective and goals. As employees productivity was higher, it would be easy to have satisfaction based on process of meeting objectives and goals will be reachable fast and easily that in turn the company will be improved and developed.